Sizing agent based on multiple bonding synergistic reinforcement mechanism, and preparation method and application thereof

By constructing a dual synergistic network of covalent bond anchoring and hydrogen bond dissipation on the surface of aramid fibers, the problems of low interfacial bonding strength and poor dynamic fatigue performance between aramid fibers and rubber matrix are solved, achieving a unity of interfacial stiffness and toughness, and improving the fatigue resistance and interfacial bonding force of composite materials.

CN122257259APending Publication Date: 2026-06-23DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610729830.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-06-23

Smart Images

  • Figure CN122257259A_ABST
    Figure CN122257259A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of fiber surface treatment, in particular to a sizing agent based on a multiple bonding synergistic enhancement mechanism and a preparation method and application thereof, comprising the following steps: dissolving a polymer containing active hydrogen functional groups in a solvent A under a protective atmosphere, stirring and dissolving to obtain a polymer solution; dropping a compound containing covalent crosslinking active sites into the polymer solution, continuously reacting to obtain a homogeneous modified solution; purifying the homogeneous modified solution to obtain a purified product; dissolving the purified product in a solvent B to obtain the sizing agent. The present application solves the technical problems of low physical adsorption bonding strength and poor fatigue resistance caused by the rigidity of a single chemical bonding interface in the existing aramid fiber surface modification technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber surface treatment technology, and in particular to sizing agents based on a multi-bonding synergistic enhancement mechanism, their preparation methods, and applications. Background Technology

[0002] Aramid fiber is a high-performance fully aromatic polyamide fiber. With its excellent specific strength, high modulus, heat resistance and dimensional stability, it has become an indispensable skeleton reinforcement material in aerospace structural components, national defense equipment and rubber products such as high-performance tires, transmission belts and conveyor belts.

[0003] However, aramid fibers have highly oriented molecular chains, high crystallinity, smooth surfaces, and a lack of active functional groups, resulting in significant chemical inertness. This leads to a marked difference in surface energy between the aramid fiber and the natural rubber matrix, poor wettability, and difficulty in forming a stable and effective interfacial bond. When the composite material is subjected to stress, stress concentration easily occurs at the weak interface, causing fiber debonding, severely limiting the reinforcing effect of aramid fibers and reducing the overall performance of the composite material.

[0004] To improve the interfacial bonding between aramid and rubber, existing technologies are mainly divided into two categories: physical modification and chemical modification. Traditional physical modification (such as plasma treatment and surface coating) is simple to operate and can improve the surface roughness and wettability of fibers. However, the interfacial bonding mainly relies on weak interactions such as van der Waals forces and mechanical interlocking, resulting in low bonding strength, poor resistance to damp heat aging, and easy interfacial slippage under shear loads. Traditional reactive chemical modification (such as surface etching and grafting modification) can build strong covalent bonds through active groups, significantly improving the static interfacial adhesion strength. However, the interfacial layer formed by these methods has a high modulus, high rigidity, and insufficient toughness.

[0005] Especially in applications such as tires and conveyor belts that are subjected to dynamic alternating loads over long periods, single covalent bond interfaces lack stress buffering and deformation capacity, failing to effectively dissipate dynamic damage energy. The interface layer is prone to brittle fracture or early fatigue failure due to stress concentration. Currently, existing sizing agents have not been able to construct a dual synergistic network of covalent bond anchoring and hydrogen bond dissipation at the interface, making it difficult to simultaneously resolve the technical contradiction between weak interfacial bonding and poor dynamic fatigue resistance. Summary of the Invention

[0006] The purpose of this invention is to provide a sizing agent based on a multi-bonding synergistic enhancement mechanism, its preparation method, and its application, thereby solving the technical problems of low physical adsorption bonding strength and poor fatigue resistance due to excessive rigidity of a single chemical bonding interface in existing aramid fiber surface modification technologies.

[0007] To achieve the above objectives, this invention provides a method for preparing a sizing agent based on a multiple bonding synergistic enhancement mechanism, comprising the following steps: S1. Under a protective atmosphere, the polymer containing active hydrogen functional groups is dissolved in solvent A and stirred to dissolve, thus obtaining a polymer solution. S2. The compound containing covalently cross-linked active sites is added dropwise to the polymer solution of S1, and the reaction is continued to obtain a homogeneous modified solution. S3. The homogeneous modified solution obtained in S2 is purified to obtain a purified product; the purified product is dissolved in solvent B to obtain a sizing agent.

[0008] Preferably, in S1, the polymer containing active hydrogen functional groups has more than 1 active hydrogen functional group, and the active hydrogen functional group includes one or more of hydroxyl, carboxyl, amino, and amide bonds.

[0009] Preferably, in S1, the polymer containing active hydrogen functional groups is a modified polymer containing side chain hydroxyl and / or amino groups, including one or more of polyvinyl alcohol, polydopamine, hyperbranched polyamide, and polyethyleneimine.

[0010] Preferably, in S1, solvent A includes one or more of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, water, and ethanol.

[0011] Preferably, in S2, the covalent crosslinking active site includes one or more of epoxy groups, isocyanates, carbon-carbon double bonds, alkynyl groups, acyl chlorides, and alkylsiloxane groups; Compounds containing covalently cross-linked active sites include one or more of the following: epoxy compounds with double bonds, isocyanate compounds, acyl chloride compounds, acyl bromide compounds, and siloxane compounds; The molar content of covalently crosslinked active sites is 1% to 20% of the active hydrogen functional groups in the polymer solution.

[0012] Preferably, the double-bonded epoxy compounds include at least one of glycidyl methacrylate, glycidyl acrylate, and 1,2-epoxy-5-hexene; the isocyanate compounds include at least one of ethyl 2-methacrylate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and ethyl 2-isocyanate; the acyl chloride compounds include at least one of acryloyl chloride, methacryl chloride, and cinnamyl chloride; the acyl bromide compounds include at least one of acryloyl bromide and methacryl bromide; and the siloxane compounds include at least one of 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

[0013] Preferably, in S3, the purification process includes one of vacuum distillation, precipitation washing, and dialysis; solvent B includes one or more of water, ethanol, and acetone.

[0014] The present invention also provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, which is prepared by the above-described method for preparing a sizing agent based on a multiple bonding synergistic enhancement mechanism.

[0015] The present invention also provides an application of a sizing agent based on a multi-bonding synergistic enhancement mechanism, such as the aforementioned sizing agent based on a multi-bonding synergistic enhancement mechanism applied to the surface modification of aramid fibers or natural rubber.

[0016] Preferably, surface modification of aramid fibers includes the following steps: (1) Surface pretreatment of aramid fibers to obtain pretreated aramid fibers; (2) Immerse the pretreated aramid fiber in (1) into the sizing agent and immerse for 1 to 60 minutes to obtain the immersed aramid fiber; (3) Take out the aramid fiber impregnated in (2) and treat it at 60~150℃ for 0.5~24h to obtain surface-modified aramid fiber; Surface modification of natural rubber includes the following steps: (4) After mixing or laying the surface-modified aramid fiber obtained in step (3) with the natural rubber matrix, hot-press vulcanization molding is carried out under the conditions of temperature of 140~180℃, pressure of 5~20MPa and time of 10~60min to obtain aramid fiber reinforced rubber composite material.

[0017] The preparation mechanism of the sizing agent of this invention: Compounds containing covalent crosslinking active sites undergo nucleophilic addition or substitution reactions with the active hydrogen functional groups (such as amino and hydroxyl groups) of polymers containing active hydrogen functional groups. By controlling the dropping rate and a low reaction temperature, the covalent crosslinking agent is kept at a low local concentration in the system, thereby inducing the crosslinking agent to preferentially graft or perform limited chain extension with the long polymer chain. The final product is a sizing agent containing covalent active groups (such as unreacted epoxy groups, isocyanates, siloxanes, or double bonds), hydrogen-bonded functional groups (such as secondary amine bonds, hydroxyl groups, amide bonds, or urethane bonds inherent in the original polymer backbone and generated in the reaction), and other polar groups (such as ether bonds and methylene groups in the polymer molecular chain).

[0018] The mechanism of modification of the sizing agent in this invention: The sizing agent of this invention first forms a homogeneous modified solution (homogeneous prepolymer) containing residual active groups through limited grafting during the synthesis stage. Subsequently, the aramid fibers are surface modified, and these residual active groups undergo secondary cross-linking driven by heat, constructing a strong interfacial covalent anchoring network. After solvent evaporation, the polymer segments of the sizing agent approach each other, and the high-density polar groups such as hydroxyl, amino, and amide groups on the chains form stable supramolecular bonds with the aramid fibers through supramolecular self-assembly. Simultaneously, the reactive functional groups at the other end of the sizing agent molecule can chemically bond with the natural rubber matrix, constructing a strong interfacial covalent anchoring network between the fiber and rubber. This interfacial anchoring system relies on the sizing agent, with one end tightly connected to the fiber through supramolecular interactions, and the other end carrying active sites that can react with the rubber matrix. This allows the modified fiber to efficiently form a stable covalent cross-linked network with the rubber matrix during subsequent composite vulcanization, and spontaneously form a dense dynamic intermolecular hydrogen bond network. The sizing agent utilizes the strong anchoring effect of covalent bonds to restrict micro-slippage, and combines the energy dissipation characteristics of hydrogen bonds to alleviate stress concentration, thereby achieving a synergistic improvement in interface stiffness and toughness, and effectively suppressing early interface failure under dynamic loads.

[0019] Therefore, the sizing agent based on the above-mentioned multi-bonding synergistic enhancement mechanism, its preparation method, and its application have the following beneficial effects: (1) The sizing agent of the present invention, by precisely controlling the ratio of covalent crosslinking active sites to active hydrogen functional groups (1%~20%), successfully constructs a dual synergistic network of covalent bond anchoring and dynamic hydrogen bond dissipation on the surface of aramid fibers. Unlike the existing technology that relies only on weak physical adsorption such as van der Waals forces or π-π stacking, and the problem of excessive interface stiffness caused by single chemical bonding, the present invention uses covalent bonds to provide strong rigid support for the interface, while the high-density dynamic hydrogen bond network acts as sacrificial bonds to efficiently dissipate destructive energy through the reversible fracture and recombination mechanism during the stress process, thus achieving a perfect unity of interface stiffness and toughness. (2) The aramid fibers treated with the sizing agent of the present invention achieve excellent interfacial bonding with the rubber matrix, resulting in a significant improvement in the H-pull-out force and peel force of the aramid fiber reinforced rubber composite material; and its interfacial layer has energy dissipation characteristics, which effectively inhibits the initiation and propagation of microcracks at the interface under dynamic load, significantly prolongs the fatigue life of the aramid fiber reinforced rubber composite material in dynamic service environment, and solves the technical problem of easy brittle debonding at the interface of the aramid fiber reinforced rubber composite material. (3) The preparation method of the present invention is simple, the reaction conditions are mild and the controllability is strong. It also eliminates the use of highly toxic aldehydes in the traditional resorcinol-formaldehyde-latex system, reduces environmental pollution and is in line with the development trend of modern chemical green chemistry. At the same time, the process has low equipment requirements and is easy to connect with existing fiber production lines, and has great potential for continuous and large-scale production.

[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0021] Figure 1 This is a SEM image of the modified aramid fiber from Application Example 1 of this invention; Figure 2 This is a SEM image of the modified aramid fiber used in Example 2 of this invention; Figure 3 This is a SEM image of the modified aramid fiber used in Example 3 of this invention; Figure 4 This is a SEM image of the modified aramid fiber in Comparative Application Example 1 of the present invention; Figure 5 This is a SEM image of the modified aramid fiber in Comparative Application Example 2 of this invention; Figure 6 This is a SEM image of the modified aramid fiber in Comparative Application Example 3 of the present invention. Detailed Implementation

[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0023] This invention provides a method for preparing a sizing agent based on a multiple bonding synergistic enhancement mechanism, comprising the following steps: S1. Under a protective atmosphere, the polymer containing active hydrogen functional groups is dissolved in solvent A and stirred to dissolve, thus obtaining a polymer solution. S2. The compound containing covalently cross-linked active sites is added dropwise to the polymer solution of S1, and the reaction is continued to obtain a homogeneous modified solution. S3. The homogeneous modified solution obtained in S2 is purified to obtain a purified product; the purified product is dissolved in solvent B to obtain a sizing agent.

[0024] In some specific embodiments of the present invention, the mass concentration of the sizing agent obtained in S3 is 0.1~10wt%.

[0025] Preferably, in S1, the polymer containing active hydrogen functional groups has more than one active hydrogen functional group, which includes one or more of hydroxyl, carboxyl, amino, and amide bonds. In this invention, having more than one active hydrogen functional group not only ensures that the polymer acts as a multidirectional bridging node in the covalent grafting reaction, preventing the crosslinking network from being interrupted due to chain termination, but also ensures that sufficient high-density polar groups remain on the molecular chain after the reaction for supramolecular self-assembly. This provides a necessary foundation for constructing multi-bonded interfaces, enabling the final sizing agent to form a crosslinking network with both high cohesive strength and excellent energy-dissipating toughness after curing.

[0026] Preferably, in S1, the polymer containing active hydrogen functional groups is a modified polymer containing side-chain hydroxyl and / or amino groups, including one or more of polyvinyl alcohol, polydopamine, hyperbranched polyamide, and polyethyleneimine. The polymer containing active hydrogen functional groups of the present invention, with its high density of side-chain polar sites and multi-branched structure, not only provides abundant anchoring nodes in the covalent grafting stage to construct a stable molecular backbone, but also forms a highly dense dynamic hydrogen bond network through supramolecular self-assembly between dense polar groups.

[0027] Preferably, in S1, solvent A includes one or more of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, water, and ethanol.

[0028] In an even more preferred embodiment, in S1, the protective atmosphere is one of argon, nitrogen, or helium.

[0029] In a further preferred embodiment, in S1, the stirring and dissolving process involves stirring at 10~80℃ for 1~3 hours.

[0030] Preferably, in S2, the covalent crosslinking active sites include one or more of epoxy groups, isocyanates, carbon-carbon double bonds, alkynyl groups, acyl chlorides, and alkylsiloxanes; Compounds containing covalently cross-linked active sites include one or more of the following: epoxy compounds with double bonds, isocyanate compounds, acyl chloride compounds, acyl bromide compounds, and siloxane compounds; The molar content of covalently cross-linked active sites is 1% to 20% of the active hydrogen functional groups in the polymer solution. This invention effectively achieves the optimal balance between interfacial covalent anchoring and hydrogen bond energy dissipation by controlling the content of covalently cross-linked active sites within this range: if the content is below 1%, the covalent cross-linking density within the system is insufficient, failing to provide adequate basic interfacial bonding strength, and the composite material is prone to interfacial debonding under load; if it is above 20%, excessive cross-linking will excessively consume active hydrogen sites and severely restrict the freedom of movement of molecular chain segments, resulting in brittle interfacial phases and loss of the energy dissipation advantage of dynamic hydrogen bonds. This preferred range ensures that a stable cross-interfacial chemical framework can be formed after the sizing agent cures into a film, while maximizing the retention of polar groups participating in supramolecular self-assembly, thereby endowing the composite material with comprehensive properties of both high interfacial bonding strength and excellent fatigue toughness.

[0031] Preferably, the double-bonded epoxy compounds include at least one of glycidyl methacrylate, glycidyl acrylate, and 1,2-epoxy-5-hexene; the isocyanate compounds include at least one of ethyl 2-methacrylate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and ethyl 2-isocyanate; the acyl chloride compounds include at least one of acryloyl chloride, methacryl chloride, and cinnamyl chloride; the acyl bromide compounds include at least one of acryloyl bromide and methacryl bromide; and the siloxane compounds include at least one of 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

[0032] The compounds of this invention, containing covalently cross-linked active sites, possess highly active functional groups that act as molecular bridges in grafting reactions with polymer chains, thereby pre-constructing a stable locally cross-linked backbone in the sizing agent solution. This effectively prevents cohesive destruction of the sizing agent interfacial layer under load, while retaining sufficient residual highly active groups in the sizing agent network to ensure chemical anchoring with the fiber and rubber matrix in subsequent composite stages, laying a solid structural foundation for the excellent interfacial properties of the composite material.

[0033] In an even more preferred embodiment, the reaction time in S2 is 1 to 10 hours.

[0034] In an even more preferred embodiment, in S2, the dropping rate is 1 drop every 10 seconds.

[0035] Preferably, in step S3, the purification process includes one of vacuum distillation, precipitation washing, and dialysis; solvent B includes one or more of water, ethanol, and acetone. This invention removes the solvent from the homogeneous modification solution through purification, effectively eliminating residual free small molecule reagents and reaction byproducts in the system, and significantly improving the purity and storage stability of the active ingredients in the sizing agent.

[0036] The present invention also provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, which is prepared by the above-described method for preparing a sizing agent based on a multiple bonding synergistic enhancement mechanism.

[0037] The sizing agent of this invention, after curing, forms a dense interfacial phase on the fiber surface that combines both "covalent anchoring" and "hydrogen bond energy dissipation" mechanisms. This sizing agent not only endows the interfacial layer with extremely high intrinsic cohesive strength and shear resistance through a stable covalent skeleton, but also provides the interface with excellent flexibility and damage buffering capacity through a dynamic hydrogen bond network. These two factors work synergistically to achieve a leap forward in the interfacial bonding performance of composite materials.

[0038] The present invention also provides an application of a sizing agent based on a multi-bonding synergistic enhancement mechanism, such as the aforementioned sizing agent based on a multi-bonding synergistic enhancement mechanism applied to the surface modification of aramid fibers or natural rubber.

[0039] Preferably, surface modification of aramid fibers includes the following steps: (1) Surface pretreatment of aramid fibers to obtain pretreated aramid fibers; (2) Immerse the pretreated aramid fiber in (1) into the sizing agent and immerse for 1 to 60 minutes to obtain the immersed aramid fiber; (3) Take out the aramid fiber impregnated in (2) and treat it at 60~150℃ for 0.5~24h to form a coating on the surface of the aramid fiber that has both covalent crosslinking and hydrogen bond network, and obtain surface modified aramid fiber. Surface modification of natural rubber includes the following steps: (4) After mixing or laying the surface-modified aramid fiber obtained in step (3) with the natural rubber matrix, hot-press vulcanization molding is carried out under the conditions of temperature of 140~180℃, pressure of 5~20MPa and time of 10~60min to obtain aramid fiber reinforced rubber composite material.

[0040] More preferably, the surface pretreatment in step (1) is to place the aramid fiber in acetone or ethanol for ultrasonic cleaning to remove surface oil and impurities; or to perform plasma etching treatment on the aramid fiber.

[0041] The surface-modified aramid fibers prepared by this invention have a surface firmly coated with a dual-functional interfacial phase that combines a strong covalent backbone and a dynamic hydrogen bond network, improving the chemical inertness of the fibers and enhancing the wettability of the fiber surface. The aramid fiber-reinforced rubber composite material prepared by this invention not only possesses extremely high basic interfacial bonding strength, but also benefits from the efficient dynamic energy dissipation buffering mechanism of the interfacial layer, effectively suppressing interfacial debonding and microcrack propagation under alternating loads, thereby significantly improving the fatigue toughness and dynamic service life of the material.

[0042] Example 1 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, polyethyleneimine is dissolved in a mixed solvent of water and ethanol and stirred at 10°C for 2 hours to obtain a polymer solution.

[0043] S2. With the molar content of covalently cross-linked active sites being 5% of the active hydrogen functional groups in the polymer solution, and the dropping rate controlled at 1 drop every 10 seconds, glycidyl methacrylate is added dropwise to the polymer solution of S1, and the reaction is continued for 4 hours to obtain a homogeneous modified solution.

[0044] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 0.5 wt%.

[0045] Example 2 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, polyethyleneimine is dissolved in a mixed solvent of water and ethanol and stirred at 10°C for 2 hours to obtain a polymer solution.

[0046] S2, the molar content of covalently cross-linked active sites is 10% of the active hydrogen functional groups in the polymer solution. The dropping rate is controlled at 1 drop every 10 seconds. Ethyl methacrylate-2-isocyanate is added dropwise to the polymer solution of S1 and the reaction is continued for 4 hours to obtain a homogeneous modified solution.

[0047] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 0.5 wt%.

[0048] Example 3 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, polyethyleneimine is dissolved in a mixed solvent of water and ethanol and stirred at 10°C for 2 hours to obtain a polymer solution.

[0049] S2, the molar content of covalently cross-linked active sites is 15% of the active hydrogen functional groups in the polymer solution. The dropping rate is controlled at 1 drop every 10 seconds. Acryloyl chloride is added dropwise to the polymer solution of S1 and the reaction is continued for 4 hours to obtain a homogeneous modified solution.

[0050] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 0.5 wt%.

[0051] Example 4 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, polyvinyl alcohol is dissolved in dimethyl sulfoxide and stirred at 40°C for 1 hour to obtain a polymer solution.

[0052] S2, the molar content of covalently cross-linked active sites is 1% of the active hydrogen functional groups in the polymer solution. The dropping rate is controlled at 1 drop every 10 seconds. Methacryl bromide is added dropwise to the polymer solution of S1 and the reaction is continued for 1 hour to obtain a homogeneous modified solution.

[0053] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 0.1 wt%.

[0054] Example 5 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, polydopamine is dissolved in N,N-dimethylacetamide and stirred at 80°C for 3 hours to obtain a polymer solution.

[0055] S2, the molar content of covalently cross-linked active sites is 20% of the active hydrogen functional groups in the polymer solution. The dropping rate is controlled at 1 drop every 10 seconds. 3-methacryloyloxypropyltrimethoxysilane is added dropwise to the polymer solution of S1 and the reaction is continued for 10 hours to obtain a homogeneous modified solution.

[0056] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 10wt%.

[0057] Example 6 This invention provides a sizing agent based on a multiple bonding synergistic enhancement mechanism, the preparation method of which includes the following steps: S1. Under nitrogen protection, the hyperbranched polyamide is dissolved in N-methylpyrrolidone and stirred at 40°C for 2 hours to obtain a polymer solution.

[0058] S2, the molar content of covalently cross-linked active sites is 10% of the active hydrogen functional groups in the polymer solution. The dropping rate is controlled at 1 drop every 10 seconds. Glycidyl acrylate is added dropwise to the polymer solution of S1 and the reaction is continued for 4 hours to obtain a homogeneous modified solution.

[0059] S3. The homogeneous modified solution obtained in S2 is subjected to vacuum distillation to remove the solvent, and dried to obtain the purified product; the purified product is dissolved in deionized water to prepare a sizing agent with a mass concentration of 5 wt%.

[0060] Application Example 1 (1) Place the aramid fiber in acetone and ultrasonically clean it to obtain the pretreated aramid fiber.

[0061] (2) Immerse the pretreated aramid fiber in (1) into the sizing agent prepared in Example 1 and immerse for 10 minutes to obtain the immersed aramid fiber.

[0062] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0063] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0064] Application Example 2 (1) Place the aramid fiber in ethanol and ultrasonically clean it to obtain the pretreated aramid fiber.

[0065] (2) Immerse the pretreated aramid fiber in (1) into the sizing agent prepared in Example 2 and immerse for 10 minutes to obtain the immersed aramid fiber.

[0066] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0067] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0068] Application Example 3 (1) Place the aramid fiber in ethanol and ultrasonically clean it to obtain the pretreated aramid fiber.

[0069] (2) Immerse the pretreated aramid fiber in (1) into the sizing agent prepared in Example 3 and immerse for 10 minutes to obtain the immersed aramid fiber.

[0070] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0071] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0072] Application Example 4 (1) The aramid fiber was subjected to plasma etching to obtain the pretreated aramid fiber.

[0073] (2) Immerse the pretreated aramid fiber in (1) into the sizing agent prepared in Example 1 and immerse for 30 minutes to obtain the immersed aramid fiber.

[0074] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 60°C for 24 hours to obtain surface-modified aramid fiber.

[0075] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 140℃, a pressure of 5MPa and a time of 10min to obtain the aramid fiber reinforced rubber composite material.

[0076] Application Example 5 (1) The aramid fiber was subjected to plasma etching to obtain the pretreated aramid fiber.

[0077] (2) Immerse the pretreated aramid fiber in (1) into the sizing agent prepared in Example 1 and immerse for 60 minutes to obtain the immersed aramid fiber.

[0078] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 150°C for 0.5h to obtain surface-modified aramid fiber.

[0079] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 180℃, a pressure of 20MPa and a time of 60min to obtain the aramid fiber reinforced rubber composite material.

[0080] Comparative Example 1 At 100°C, polyethylene was dissolved in decahydronaphthalene and stirred until completely dissolved to prepare a homogeneous solution with a concentration of 0.5 wt%, which was used as a sizing agent.

[0081] Comparative Example 2 Polystyrene was dissolved in tetrahydrofuran at 60°C and stirred until completely dissolved to prepare a homogeneous solution with a concentration of 0.5 wt%, which was used as a sizing agent.

[0082] Comparative Example 3 At 60°C, polystyrene-polyisoprene block copolymer was dissolved in tetrahydrofuran and stirred until completely dissolved to prepare a homogeneous solution with a concentration of 0.5 wt%, which was used as a sizing agent.

[0083] Comparative Application Example 1 (1) Place the aramid fiber in acetone and ultrasonically clean it to obtain the pretreated aramid fiber.

[0084] (2) The aramid fibers pretreated in (1) were immersed in the sizing agent prepared in Comparative Example 1 and immersed for 10 min to obtain the immersed aramid fibers.

[0085] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0086] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0087] Comparative Application Example 2 (1) Place the aramid fiber in acetone and ultrasonically clean it to obtain the pretreated aramid fiber.

[0088] (2) The aramid fibers pretreated in (1) were immersed in the sizing agent prepared in Comparative Example 2 and immersed for 10 minutes to obtain the immersed aramid fibers.

[0089] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0090] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0091] Comparative Application Example 3 (1) Place the aramid fiber in acetone and ultrasonically clean it to obtain the pretreated aramid fiber.

[0092] (2) The aramid fibers pretreated in (1) were immersed in the sizing agent prepared in Comparative Example 3 and immersed for 10 minutes to obtain the immersed aramid fibers.

[0093] (3) Take out the aramid fiber impregnated in (2) and treat it in an oven at 80°C for 12 hours to obtain surface-modified aramid fiber.

[0094] (4) After the surface-modified aramid fiber obtained in step (3) is laid up with the natural rubber matrix, it is hot-pressed and vulcanized at a temperature of 160℃, a pressure of 10MPa and a time of 30min to obtain the aramid fiber reinforced rubber composite material.

[0095] Performance testing The aramid fibers obtained in Application Examples 1-3 and Comparative Application Examples 1-3 were characterized using scanning electron microscopy, such as... Figure 1-6 As shown, compared with the original smooth and clean surface of the untreated aramid fiber, the surfaces of each modified fiber exhibit varying degrees of roughness, proving that the sizing agent has been successfully adhered.

[0096] The aramid fiber reinforced rubber composites prepared in Application Examples 1-3 and Comparative Application Examples 1-3 were tested using the H-pull test method to determine the interfacial bonding force between the fiber and the rubber, and the results are shown in Table 1.

[0097] Table 1. H-pull-out force of rubber composites with different aramid fiber reinforcements

[0098] As shown in Table 1, the H-extraction force of Application Examples 1-3 is significantly better than that of Comparative Application Examples 1-2, which rely solely on physical adsorption. In particular, Application Example 2, which uses a preferred crosslinking ratio, has an interfacial bonding force as high as 32.23 N, far exceeding that of Comparative Application Example 3 (23.21 N), which uses a traditional rigid covalent network. This demonstrates that the sizing agent of the present invention effectively overcomes the interfacial debonding defects easily caused by traditional single or pure rigid modification layers by successfully constructing a dual synergistic interfacial phase with strong covalent anchoring and high energy consumption of hydrogen bonding on the fiber surface, thereby improving the interfacial performance of the composite material from the microstructure perspective.

[0099] The 180° peel strength of the aramid fiber reinforced rubber composites prepared in Application Examples 1-3 and Comparative Application Examples 1-3 was tested using the 180° peel strength test method. The results are shown in Table 2.

[0100] Table 2. 180° peel force of rubber composites reinforced with different aramid fibers

[0101] As shown in Table 2, the 180° peel force of Application Examples 1-3 is generally better than that of Comparative Application Examples 1-3, with Application Example 2 having the highest peel force of 13.98 N. This indicates that the sizing agent of the present invention can effectively improve the interfacial bonding performance of composite materials by constructing an interfacial phase with strong covalent anchoring and high energy consumption of hydrogen bonding.

[0102] The strength retention rate of aramid fiber reinforced rubber composites prepared in Application Examples 1-3 and Comparative Application Examples 1-3 after 1000 tensile cycles was tested using tensile testing methods. The results are shown in Table 3.

[0103] Table 3 Strength retention rate of rubber composites reinforced with different aramid fibers after 1000 tensile cycles

[0104] As shown in Table 3, the strength retention rates of Application Examples 1-3 are generally higher than those of Comparative Application Examples 1-3. Among them, the strength retention rate of Application Example 2 reaches 76.8%, while the strength retention rates of Comparative Application Examples 1-3 are all less than 50%. This indicates that the sizing agent of the present invention can effectively dissipate stress and inhibit the accumulation of interfacial fatigue damage under cyclic loading, thereby significantly improving the fatigue resistance of the composite material.

[0105] Therefore, this invention employs the aforementioned sizing agent based on a multi-bonding synergistic enhancement mechanism, its preparation method, and its application. By introducing multiple reactive components, the sizing agent constructs a synergistic mechanism of covalent bond anchoring and hydrogen bond energy dissipation, achieving a simultaneous improvement in interfacial stiffness and toughness. Test results show that the H-pull-out force and peel strength between aramid fibers and the rubber matrix are significantly improved after treatment with the sizing agent of this invention, and it can effectively suppress early failure caused by interfacial fatigue.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a sizing agent based on a multi-bonding synergistic enhancement mechanism, characterized in that: Includes the following steps: S1. Under a protective atmosphere, the polymer containing active hydrogen functional groups is dissolved in solvent A and stirred to dissolve, thus obtaining a polymer solution. S2. The compound containing covalently cross-linked active sites is added dropwise to the polymer solution of S1, and the reaction is continued to obtain a homogeneous modified solution. S3. The homogeneous modified solution obtained in S2 is purified to obtain the purified product; The purified product was dissolved in solvent B to obtain a sizing agent.

2. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 1, characterized in that: In S1, the polymer containing active hydrogen functional groups has more than 1 active hydrogen functional group, which includes one or more of hydroxyl, carboxyl, amino, and amide bonds.

3. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 2, characterized in that: In S1, the polymer containing active hydrogen functional groups is a modified polymer containing side chain hydroxyl and / or amino groups, including one or more of polyvinyl alcohol, polydopamine, hyperbranched polyamide, and polyethyleneimine.

4. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 1, characterized in that: In S1, solvent A includes one or more of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, water, and ethanol.

5. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 1, characterized in that: In S2, the covalent cross-linking active sites include one or more of the following: epoxy group, isocyanate group, carbon-carbon double bond, alkynyl group, acyl chloride, and alkylsiloxane; Compounds containing covalently cross-linked active sites include one or more of the following: epoxy compounds with double bonds, isocyanate compounds, acyl chloride compounds, acyl bromide compounds, and siloxane compounds; The molar content of covalently crosslinked active sites is 1% to 20% of the active hydrogen functional groups in the polymer solution.

6. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 5, characterized in that: The double-bonded epoxy compounds include at least one of glycidyl methacrylate, glycidyl acrylate, and 1,2-epoxy-5-hexene; the isocyanate compounds include at least one of ethyl 2-methacrylate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and ethyl 2-isocyanate; the acyl chloride compounds include at least one of acryloyl chloride, methacryloyl chloride, and cinnamoyl chloride; the acyl bromide compounds include at least one of acryloyl bromide and methacryloyl bromide; and the siloxane compounds include at least one of 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

7. The method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism according to claim 1, characterized in that: In S3, the purification process includes one of vacuum distillation, precipitation washing, and dialysis; solvent B includes one or more of water, ethanol, and acetone.

8. A sizing agent based on a multi-bonding synergistic enhancement mechanism, characterized in that: It is prepared by the method for preparing the sizing agent based on the multi-bonding synergistic enhancement mechanism as described in any one of claims 1-7.

9. An application of a sizing agent based on a multi-bonding synergistic enhancement mechanism, characterized in that: The sizing agent based on a multi-bonding synergistic enhancement mechanism as described in claim 8 is applied to the surface modification of aramid fibers or natural rubber.

10. The application of a sizing agent based on a multi-bonding synergistic enhancement mechanism according to claim 9, characterized in that: Surface modification of aramid fibers includes the following steps: (1) Surface pretreatment of aramid fibers to obtain pretreated aramid fibers; (2) Immerse the pretreated aramid fiber in (1) into the sizing agent and immerse for 1 to 60 minutes to obtain the immersed aramid fiber; (3) Take out the aramid fiber impregnated in (2) and treat it at 60~150℃ for 0.5~24h to obtain surface-modified aramid fiber; Surface modification of natural rubber includes the following steps: (4) After mixing or laying the surface-modified aramid fiber obtained in step (3) with the natural rubber matrix, hot-press vulcanization molding is carried out under the conditions of temperature of 140~180℃, pressure of 5~20MPa and time of 10~60min to obtain aramid fiber reinforced rubber composite material.